2015
DOI: 10.1002/app.42814
|View full text |Cite
|
Sign up to set email alerts
|

Depolymerization protocol for linear, branched, and crosslinked end‐of‐life silicones with boron trifluoride diethyl etherate as the depolymerization reagent

Abstract: An important issue for current society is the accumulation of large amounts of end-of-life polymers, which are mainly deposited in landfills, converted by thermal recycling or down cycling to low-quality materials. In contrast to that, the feedstock recycling of end-of-life polymers to produce new high-quality polymers is only applied to a small portion of waste. In more detail, lowmolecular weight chemicals are generated by this methodology; they can be polymerized in a second step to produce new highquality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…24−32 These methods range from thermal 27−33 to chemical breakdown (by catalytic or stoichiometric reagent) processes. 5,[27][28][29]34 The earliest methods used thermal energy, often with steam, to impart breakdown to both identifiable and unidentifiable components. 22,35−39 These methods typically result in a broad distribution of products.…”
Section: Introductionmentioning
confidence: 99%
“…24−32 These methods range from thermal 27−33 to chemical breakdown (by catalytic or stoichiometric reagent) processes. 5,[27][28][29]34 The earliest methods used thermal energy, often with steam, to impart breakdown to both identifiable and unidentifiable components. 22,35−39 These methods typically result in a broad distribution of products.…”
Section: Introductionmentioning
confidence: 99%
“…Several depolymerization pathways and reagents have been tested. [145][146][147] Döhlert et al 148 have shown that boron trifluoride dietherate (BF 3 •OEt 2 ) is able to break the siloxane bond in hexamethyl disiloxane (1) -Scheme 2(a). Based on this, the depolymerization of poly(dimethyl siloxane) (4) has also been successfully tested (Scheme 2(b)).…”
Section: Guidelines For Disposal Of Silica Aerogelsmentioning
confidence: 99%
“…Environmental Science: Nano Critical review Following this work, the same group has concluded that the depolymerizing effect of BF 3 •OEt 2 (2) does not depend on the structure of the polysiloxane, thus it can also be used for branched and crosslinked polysiloxanes. 147 In all reported cases, the depolymerization products can be used for the synthesis of new high-quality polymers.…”
Section: Guidelines For Disposal Of Silica Aerogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enthaler and colleagues reported synthetic protocols for the depolymerization of various silicone oils (with M n from 0.5 to 110 kDa). They used benzoyl fluoride, boron trifluoride dietherate, a fatty acid anhydride, or combinations of benzoyl chloride or benzoic anhydride with KF to synthesize fluorosilane and fluorodisiloxane derivatives of Me 2 SiF 2 and (Me 2 SiF) 2 O for linear polymers, and Me 2 SiF 2 and SiF 4 for branched polymers. The obtained fluorinated compounds are attractive starting materials and can be easily polymerized in the presence of H 2 O and NaOH to produce new silicones and NaF . Depolymerization methods were also developed in which catalytic amounts of FeCl 3 or ZnX 2 (X = acac, OAc, or OTf) were used. , The same group also reported the use of poly­(methylhydrosiloxane) in H 2 evolution by methanolysis, deoxygenation of sulfoxides to sulfides, and hydrodeoxygenation of fatty esters to hydrocarbons, prior to the depolymerization procedure described above .…”
Section: Introductionmentioning
confidence: 99%